The business of paradigms - Barker, Joel Arthur; Infinity Ltd.; Charthouse International Learning (Burnsville : Charthouse International Learning, 1991)
Barker explores how hidden barriers to new ideas limit our ability to successfully anticipate the future
Keywords: Social prediction; Paradigms (Social sciences); Social change